Citizenship and the environment - Dobson, Andrew (Oxford University Press, 2003)
In this text, Andrew Dobson argues that ecological citizenship cannot be fully articulated in terms of the two great traditions of citizenship - liberal and civic republican - and develops an original theory of citizenship, which he calls 'post-cosmopolitan'.